PERLINDUNGAN HAK ASASI ANAK SEBAGAI PELAKU DAN KORBAN TINDAK PIDANA (Peran Dan Fungsi Komisi Nasional Perlindungan Anak) - Fransiska Novita Eleanora (JURNAL MITRA MANAJEMEN, 2017)
AbstractSince human beings are born into the world, human rights are attached, the rights of human beingsthat have been acquired and brought together with the birth or presence in public life. Neither thechild, the right to life has been there since they were in the womb, and if the child is a crime, theremust be protection. The purpose of this paper to determine the role and functions of the National Commission on Child Protection (institution child) in providing protection related rights of childrenas perpetrators and victims of crime. The method is a normative legal research or research library is aresearch study that examines the document, which uses a variety of secondary information such aslegislation, court decisions, legal theory, and may be the opinion of the scholars. As a result of thenational commission for child protection provides protection for children as perpetrators and victimsof crime in terms of discrimination, exploitation, both economic and sexual, neglect, cruelty,violence, persecution, injustice and abuse others. keywords; protection, human rights, child